The Indonesian Cyber Diplomacy: ASEAN-Japan Online Cyber Exercise - Saputri, Dessy Permatasari; Surryanto D. W.,; Helda Risman, (Technium Social Sciences Journal, 2020)
The development of information and communication technology is growing both globally and regionally making it easier for everyone to access all information and communicate without knowing the limits even though many benefits can be obtained. The reality, in turn, gives a negative impact such as personal crime, theft, and data falsification to attack systems or forms of state infrastructure. Cyber threats that occur in Indonesia include racial riots in 1998 which Indonesia had to fight with hackers from China and Taiwan. Besides, the Indonesian government must also face espionage that done by Australia through its representative building in Jakarta. Therefore, cooperation is needed through the defense diplomacy process as a way to deal with all forms of cyber threats in Indonesia called cyber diplomacy. This study uses qualitative research methods through library research intending to analyze concepts and descriptions of cyber diplomacy. Cyber diplomacy conducted by Indonesia is involvement through the ASEAN-Japan Online Cyber Exercise program which is still at the level of developing the skills of cyber personnel but has not touched on the policy domain to regulate program development. Then there needs to be further development by bringing this program to the ADMM forum.